Investigation of structural mechanisms of laser-written waveguide formation through third-harmonic microscopy - Guan, J; Liu, X; Booth, M (Optical Society of America, 2019)
The mechanisms of laser-induced modification of transparent materials are complex combinations of different processes that depend on the material itself and a range of processing parameters. As such, the mechanisms are still subject to ongoing study. We use a custom-built adaptive third-harmonic generation (THG) microscope to study those mechanisms. New femtosecond-laser-written phenomena are revealed through this method of imaging. This Letter, together with previous reports by Miyamoto Opt. Express 24, 25718 (2016) [CrossRef] and Fernandez J. Phys. D 48, 155101 (2015) [CrossRef] suggest that the distribution of the generated plasma during writing is responsible for the newly revealed phenomena.